Education Provision for Indigenous and Minority Heritage Languages Revitalisation: A Study Focusing on Saami and Scottish Gaelic - Beaton, Mhairi C.; Helander, Hanna; Keskitalo, Pigga (Springer International Publishing, 2023)
Abstract This chapter provides a comparative study of education provision for the Indigenous language of Saami and the minority heritage of Scottish Gaelic. Due to historical factors, both languages are considered endangered according to UNESCO listings. Whilst North Saami and Scottish Gaelic receive government support, which would appear to be providing a reasonably stable position at least within their geographically core areas, assimilation continues resulting in the overall numbers of speakers remaining small. As education is viewed as key to the promotion of both languages, following an introduction to the background historical and societal context of both language contexts, the chapter presents educational practices and challenges in education for comparison over the past forty years. The comparative study highlights that similarities between these two languages exist in language revitalisation efforts to reverse language shift but the forms vary. The chapter concludes with some emerging recommendations for the successful maintenance and revitalisation of minority heritage and Indigenous languages in the twenty-first century despite the continued dominance of surrounding majority languages.